2020
DOI: 10.2196/21268
|View full text |Cite
|
Sign up to set email alerts
|

Potential of HIV Self-Sampling to Increase Testing Frequency Among Gay, Bisexual, and Other Men Who Have Sex With Men, and the Role of Online Result Communication: Online Cross-Sectional Study

Abstract: Background Late HIV diagnosis remains frequent among the gay, bisexual, and other men who have sex with men (GBMSM) population across Europe. HIV self-sampling could help remove barriers and facilitate access to testing for this high-risk population. Objective We assessed the capacity of HIV self-sampling to increase the testing frequency among GBMSM living in Denmark, Germany, Greece, Portugal, Romania, and Spain, and evaluated the role of new technolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Thirty-three studies identified home-based self-testing or self-sampling as the preferred method of testing [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 26 , 29 , 31 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] ( Table 2 ). Three randomised controlled trials (RCT) found that HIVST increased testing frequency, and therefore was preferred by MSM compared to usual testing [ 17 , 21 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-three studies identified home-based self-testing or self-sampling as the preferred method of testing [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 26 , 29 , 31 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] ( Table 2 ). Three randomised controlled trials (RCT) found that HIVST increased testing frequency, and therefore was preferred by MSM compared to usual testing [ 17 , 21 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was an average use of 3.9 self-tests per person in the free self-testing group over the 15-month period, which was an increase of 1.7 tests per person compared to the testing as usual group [ 17 ]. Another US RCT randomised 65 HIV-negative MSM into three groups: HIVST kits by mail with a follow-up call from a counsellor (eTEST), standard HIVST kits with no follow-up (standard), or letters containing information about HIV testing locations (control) [ 53 ]. Delivery of HIVST kits by post at 3-month intervals increased testing, with all participants from the eTEST and standard groups testing at least once during the 7-month period compared to 72% of the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Le Roux (2017) discută despre implicarea actorilor religioși în educarea cu privire la HIV în țări cu prevalență scăzută (Rusia, Armenia și România). Chestionând un eșantion de homosexuali, bisexuali, și alți bărbați care întrețin relații sexuale cu bărbați (GBMSM), din șase țări europene, inclusiv România, Maté et al (2020) propun o metodă de testare personală pentru HIV. Manolescu et al (2019) atrag atenția asupra pericolului indus de sifilis asupra femeilor însărcinate din România și a nou-născuților acestora.…”
Section: Cercetări Despre Boli șI Infecții (Inclusiv Criza Covid-19)unclassified
“…Home-based sexual health care consists of self-collection of samples, and additional online sexual health counseling, for example about PrEP and chemsex. Home-based alternatives for testing can overcome perceived and experienced barriers among MSM for STI/HIV testing at STI clinics such as privacy, confidentiality, and time-constraints ( 9 , 10 ). Home-based care options enable continual access to care for MSM who seek sexual health care, and due to COVID-19 restrictions, personal needs, or other reasons, experience barriers to clinic-based testing or sexual health counseling.…”
Section: Introductionmentioning
confidence: 99%